Краткий анализ поведения глобальных функций распределения партонов при малом и большом x - Jahan, Akbari; Neog, Diptimonta (Recent Contributions to Physics, 2023)
Parton distribution functions (PDFs) inscribe details about the hadronic substructure in terms of partons, quarks and gluons collectively, which are the fundamental degrees of freedom of Quantum Chromodynamics (QCD), the theory of strong interactions. Study of PDFs has led to a better comprehension of the partonic structure of hadrons and the proton structure function in deep inelastic scattering. Understanding parton densities within the hadrons is vital to estimate the hard-scattering process results. Owing to theoretical and experimental limitations, PDFs cannot be computed from the first principles. The global analysis of parton distribution functions, therefore, requires an unrelenting endeavour. The aim of the present work is to have a comparative study of the PDFs from the plots obtained using APFEL, which is a PDFs evolution library. We discuss the graphical analyses as well as comparisons of the three global PDFs sets, viz. CT10, MSTW2008 and NNPDF30, in a wide range of momentum fraction x and energy scale Q. A comparative analysis of gluons extracted from these global fits has also been done.